Application of MALDI-TOF MS Profiling Coupled With Functionalized Magnetic Enrichment for Rapid Identification of Pathogens in a Patient With Open Fracture - Ying, Jichong; Gao, Wenjing; Huang, Dichao; Ding, Chuanfan; Ling, Ling; Pan, Tao; Yu, Shaoning (Frontiers in Chemistry, 2021)
Posttraumatic infections can occur in orthopedic trauma patients, especially in open fractures. Rapid and accurate identification of pathogens in orthopedic trauma is important for clinical diagnosis and antimicrobial treatment. Matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) has been successfully used for first-line identification of pathogens grown on culture plates. However, for direct analysis of liquid clinical specimens, pre-purification of the sample is necessary. Herein, we investigated the feasibility of coupling Fc-MBL@Fe3O4 enrichment with MALDI-TOF MS profiling in identification of pathogens in liquid cultured samples. This method is successfully used for identification of pathogens in a patient with an open leg fracture obtained at sea. Pathogens were enriched by Fc-MBL@Fe3O4 from briefly pre-cultured liquid media and identified by MALDI-TOF MS. We identified an opportunistic pathogen, Vibrio alginolyticus, which is uncommon in clinical orthopedic trauma infection but exists widely in the sea. Therefore, combining Fc-MBL@Fe3O4 enrichment and MALDI-TOF MS profiling has great potential for direct identification of microbes in clinical samples.